2019
DOI: 10.1038/s41467-019-10781-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the role of the chaperonin CCT in mTOR complex assembly

Abstract: The mechanistic target of rapamycin (mTOR) kinase forms two multi-protein signaling complexes, mTORC1 and mTORC2, which are master regulators of cell growth, metabolism, survival and autophagy. Two of the subunits of these complexes are mLST8 and Raptor, β-propeller proteins that stabilize the mTOR kinase and recruit substrates, respectively. Here we report that the eukaryotic chaperonin CCT plays a key role in mTORC assembly and signaling by folding both mLST8 and Raptor. A high resolution (4.0 Å) cryo-EM str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 70 publications
9
66
3
Order By: Relevance
“…For example, CCT6B , a subunit of the chaperonin containing TCP1 (CCT) complex (also known as TRiC), is a 5′TOP mRNA, and several other CCT mRNAs only slightly missed our stringent criteria for defining 5′TOP mRNAs (e.g., CCT7 has a TOPscore of 8.4, was relatively translationally repressed 1.4-fold by Torin2 in wild-type, and was not relatively translationally repressed by Torin2 in larp1 ). The CCT complex promotes assembly of many proteins, including RAPTOR and LST8 ( Cuéllar et al, 2019 ), but is most famously associated with assembly of actin and tubulin subunits ( Balchin et al, 2018 ; Dekker et al, 2008 ; Yam et al, 2008 ). In mammals, TOR regulates CCT complex function by promoting phosphorylation of the CCT complex ( Abe et al, 2009 ), indicating that metabolic regulation of CCT complex activity by TOR may occur through multiple signal transduction pathways in different eukaryotic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CCT6B , a subunit of the chaperonin containing TCP1 (CCT) complex (also known as TRiC), is a 5′TOP mRNA, and several other CCT mRNAs only slightly missed our stringent criteria for defining 5′TOP mRNAs (e.g., CCT7 has a TOPscore of 8.4, was relatively translationally repressed 1.4-fold by Torin2 in wild-type, and was not relatively translationally repressed by Torin2 in larp1 ). The CCT complex promotes assembly of many proteins, including RAPTOR and LST8 ( Cuéllar et al, 2019 ), but is most famously associated with assembly of actin and tubulin subunits ( Balchin et al, 2018 ; Dekker et al, 2008 ; Yam et al, 2008 ). In mammals, TOR regulates CCT complex function by promoting phosphorylation of the CCT complex ( Abe et al, 2009 ), indicating that metabolic regulation of CCT complex activity by TOR may occur through multiple signal transduction pathways in different eukaryotic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the control of the activity of the PIKKs by their respective regulatory proteins might involve an allosteric mechanism mediated by binding to the N-HEAT domain, which can also serve as a platform for binding of specific proteins. domains, an interaction which is required for proper folding and mTORC1 assembly [124]. This interaction was not detected for mTOR, Rictor or mSin1.…”
Section: Beyond Cell Growth: Tor As a Pikkmentioning
confidence: 92%
“…Beyond mTOR, proper folding of the other mTORC1 subunits is also required. Recently, it has been shown that both mLst8 and Raptor bind to the chaperonin CCT via their β-propeller/WD40 domains, an interaction which is required for proper folding and mTORC1 assembly [124]. This interaction was not detected for mTOR, Rictor or mSin1.…”
Section: Beyond Cell Growth: Tor As a Pikkmentioning
confidence: 99%
“…Importantly, depleting CCT subunits in an autophagydeficient background did not further increase the aggregation of mutant huntingtin or the aggregation of another polyglutaminecontaining protein ataxin 3 (Pavel et al, 2016). Furthermore, the CCT oligomer is involved in folding components of the mTORC complex, thus affecting mTORC assembly (Cuellar et al, 2019). Therefore, loss of CCT oligomer could influence several cellular processes including autophagy via mTORCmediated pathways.…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%